Music in the life of nursing home residents. Issue 3 (2nd September 2022) - Paolantonio, Paolo; Pedrazzani, Carla; Cavalli, Stefano; Williamon, Aaron
ABSTRACT: Background: Making and listening to music can be beneficial for older adults. However, little is known about how and to what extent those who live in nursing homes have access to music and the functions that music plays in their lives. Methods: This study involved 20 residents who volunteered from six nursing homes in Switzerland. Each resident was interviewed, and the data were analysed using thematic analysis. Results: For many residents, their access to music decreased after moving into their nursing home, and many of them wanted more musical experiences in their daily lives, both with music from their pasts and with unfamiliar repertoire. Music was strongly connected to their sense of identity and elicited positive emotions. Musical activities offered by the nursing homes also stimulated social interactions. Conclusions: Music plays a central role in facilitating positive wellbeing and quality of life in nursing homes.